PENGELOLAAN PEMBELAJARAN TUNTAS DI SEKOLAH DASAR STANDAR NASIONAL GUNTUR 1 DEMAK - Triyono , Triyono (2011)
This purpose of the research is to describe (1) the characteristics of planning teachers in the mastery learning in elementary school in SD SN Guntur 1 Demak (2) the characteristics implementation of mastery learning in elementary school in SD SN Guntur 1 Demak (3) the characteristics of the evaluation mastery learning in primary school completion in SD SN Guntur 1 Demak. This research used qualitative research. The research was conducted in SD SN Guntur 1 Guntur District Demak regency. Resource persons in this study of teachers, principals and elementary school students in SD SN Guntur 1 Demak. Collection data methods using in-depth interviews, participant observation and documentation. Data analysis started from (1) collection data (2) reduction data (3) presentation data and (4) conclusion. Test the validity of the data using the credibility transterability, conformability and dependability. The results indicated are (1) The characteristics of planning mastery learning in SD SN Guntur 1 Demak. Master plan implementation of learning with reference to the standard of competence and basic competence in accordance with the needs and characteristics of learners. In planning teachers are given full authority to design learning activities teaching which contains, among other identities, indicators, learning objectives, methods and techniques, media and learning resources, assessment and other supporting capacity and principals provide direction, guidance and assessment. (2) Characteristics feature implementation of mastery learning in SD SN Guntur 1 Demak. In mastery learning of interaction between teacher and student is going well students can express opinions and be motivated to resolve the matter lesson in a basic competency with completely. Learning to use although the principle of individual mastery activites aimed at group of learnes are classical, so that with the implementation mastery learning the development potential of each learner optimally. (3) The characteristics of evaluating lessons completion in SD SN Guntur 1 Demak. Evaluation using continuous assessment characteristics are replications conducted of one or more basic competence, test results of tests analyzed and the follow through in the from of repair and remedial programs enrichment. Deuteronomy includes aspects of cognitive, psychomotor and affective aspects. The evaluation was conducted through assignments, daily tests, the middle semester and repeat the final semester for classes IV and the national exam for Class VI.